2022
DOI: 10.3390/app12157858
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Characteristics of Ultra-High-Performance Concrete Containing Carbon-Based Materials

Abstract: Recently, carbon materials with unique properties, such as high tensile strength and electrical conductivity, have been extensively investigated for the multi-functionalization of concrete. Previous studies mainly focused on improving the performance of normal-strength concrete using carbon nanomaterials, such as carbon nanotubes and graphene nanoplates. Therefore, this study analyzed the effect of carbon materials on ultra-high-performance concrete (UHPC) mixed with steel fibers, which has an outstanding mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 47 publications
1
0
0
Order By: Relevance
“…Jung et al [14] reported an enhancement in the electrical conductivity of UHPC up to the percolation threshold due to CNT incorporation, which is consistent with the literature [39,40]. Lim et al [32] indicated that although the electrical conductivity of UHPC increased as the content of CNTs increased, its conductivity was not as high. Jung et al [31], in turn, registered a consistent reduction in the electrical resistivity of UHPC at contents up to 0.8% by weight of cement, which they attributed to the stable dispersion of CNTs in aqueous suspension in the cement matrix.…”
Section: Electrical Conductivity and Resistivitysupporting
confidence: 70%
“…Jung et al [14] reported an enhancement in the electrical conductivity of UHPC up to the percolation threshold due to CNT incorporation, which is consistent with the literature [39,40]. Lim et al [32] indicated that although the electrical conductivity of UHPC increased as the content of CNTs increased, its conductivity was not as high. Jung et al [31], in turn, registered a consistent reduction in the electrical resistivity of UHPC at contents up to 0.8% by weight of cement, which they attributed to the stable dispersion of CNTs in aqueous suspension in the cement matrix.…”
Section: Electrical Conductivity and Resistivitysupporting
confidence: 70%
“…The conductivity is related to the addition of MWCNTs in the cement composite. The nanotubes added to the cement mixture develop a connection network that allows lower resistance in the electrical current until a percolation limit is reached [43,67].…”
Section: Electrical Measurementsmentioning
confidence: 99%
“…High Cost and Economic Justification Gap: The production cost of UHPC is notably higher, amounting to a minimum of 6.6 times that of ordinary concrete [69,70] Moreover, limited manufacturers, such as Lafarge, offer comprehensive industrial support for the requisite raw materials [70][71][72][73]. Nonetheless, intricate applications such as concrete-filled steel tubes (CFST) for columns and steel-concrete-steel sandwich composites are garnering attention [72,73].…”
mentioning
confidence: 99%